2015
DOI: 10.11648/j.ajbio.20150303.12
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of High Acetic Acid-Producing Bacteria in Ivorian Cocoa Fermentation and Analysis of Their Response to Fermentative Stress

Abstract: Acetic acid produced during cocoa fermentation impact strongly the quality of fermented and dried cocoa beans and chocolate. The objective of this study was to analyze acid production in Acetic acid bacteria (AAB) and their response to fermentative conditions. AAB strains were isolated from cocoa fermentation and screened for acid production on both solid and liquid media. From 444 isolates, 15 strains yielded 2 to 38.1 g/L of acid in liquid medium. The best acid producers were identified by biochemical typing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These data clearly explains why Afoakwa et al (2013) found that acidity level, due probably to acetic acid, was highest at 40 °C 35 °C b 3 days of fermentation. In addition, in previous studies, Soumahoro et al (2015) reported a good growth capacity of these strains at pH values ranged 3 to 7. Consequently, variation of the pH values during a cocoa fermentation essay could not affect acetic acid production capacity of tested strains.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…These data clearly explains why Afoakwa et al (2013) found that acidity level, due probably to acetic acid, was highest at 40 °C 35 °C b 3 days of fermentation. In addition, in previous studies, Soumahoro et al (2015) reported a good growth capacity of these strains at pH values ranged 3 to 7. Consequently, variation of the pH values during a cocoa fermentation essay could not affect acetic acid production capacity of tested strains.…”
Section: Resultsmentioning
confidence: 62%
“…Our results also showed that no acetic acid production was observed at temperature above 45 °C. Yet, in previous studies, Soumahoro et al (2015) demonstrated that all tested strains are able to growth at 45 °C and strains 49 D, 139 D and 56 AB at 50 °C. On the other hand, Saeki et al (1997) demonstrated the increase in stability with increase of temperature (above 50 °C) of enzymes notably alcohol dehydrogenase and aldehyde dehydrogenase implicated in conversion of ethanol into acetic acid (Tayama et al, 1989).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Ho V. , Zhao, Srzednicki, & Fleet, 2013). Among these microorganisms, yeasts are essentials because considered as initiators of this process (Soumahoro, et al, 2015. Ho, Zhao, & Fleet, 2014.…”
Section: Introductionmentioning
confidence: 99%